Plasma cortisol concentrations in calves delivered from uterine torsion affected buffaloes - SATHYA, A; PRABHAKAR, S; GHUMAN, S P S; MISRA, Y (The Indian Journal of Animal Reproduction, 2023)
A study on 65 buffaloes having uterine torsion was conducted to estimate the plasma cortisol concentraticil in 6 live calves delivered from them. Two calves delivered normally after induction of parturition were also included for comparison. Plasma cortisol concentration in calves delivered from dams after detorsion of uterus and manipulations were non-significantly higher than normally delivered calves. Number of rolls required for detorsion of uterus also increased plasma cortisol concentration in calves. It thus appeared that estimation of plasma cortisol concentration may be a good prognostic i dicator for fetal _survival following handling of dystocia.